Instructor-Driven Causes and Impacts of Grade Inflation in Philippine Higher Education - Giray, Louie (Indonesian Journal of Social Research (IJSR), 2024)
Grade inflation in Philippine higher education is a growing concern, with instructors increasingly assigning higher grades to students. This paper investigates instructor-driven causes behind grade inflation and its impacts. Autoethnography was used as a method. The study locale was public state universities and colleges in Taguig City and Muntinlupa City, Philippines; data collection involved immersion, a personal diary, and informal discussions with faculty and students. Thematic analysis, guided by research inquiries, unveiled the factors driving this trend. Results suggest compassionate grading, influenced by a desire to support students facing challenges, fosters inflated success perceptions. Laziness, apathy, and sycophancy also contribute to lax grading, hindering genuine academic growth. Meanwhile, the impacts extend beyond academia, affecting graduates' skill acquisition and potentially dissatisfying employers. Recommendations advocate for enhanced accountability among instructors through rigorous evaluation systems and continuous professional development to safeguard academic standards. Combating grade inflation necessitates collaborative efforts to uphold education quality and integrity, benefiting students, institutions, and society.